Anglican Rites of Consecration and the Delineation of Sacred Space, ca. 1689–1735. Issue 2 (June 2021) - Spicer, Andrew
Abstract : Between 1712 and 1715, the Convocation of the Church of England attempted to replace the existing informal orders used for the consecration of churches, chapels, and churchyards with a single uniform rite. While these efforts have been associated with the erection of the Fifty New Churches to provide for the populous and expanding suburbs of London and Westminster, the discussions actually arose out of the political divisions between the bishops and the Lower House of Convocation. The efforts to establish an official order of consecration was also a response to the changed ecclesiastical climate that followed the Toleration Act of 1689, which allowed for the registration of Dissenter chapels. The Established Church found its religious hegemony threatened and the particular status of its places of worship, achieved through consecration, challenged. The church responded to the criticism of their existing forms of consecration by reforming the liturgy as well as demonstrating the historical and legal basis for the practice. The sermons preached at the consecration or reopening of these churches provided a further opportunity for the clergy to justify the ceremony as well as to draw comparisons between these churches and Dissenting meetinghouses.